Determinants of job satisfaction: internal communication relationships in improving employee performance - Karsikah; Roni Kambara; Didit Haryadi; Agus David Ramdansyah (Enrichment : Journal of Management, 2023)
One of the efforts in improving employee performance is by building effective communication, among others, with internal communication between leaders and subordinates. This study aims to test and analyze the effect of job satisfaction, and internal communication on employee performance. The PLS-SEM approach was used in this study. The results of this study indicate that internal communication has a positive and significant effect on employee performance. Internal communication has a positive and significant effect on job satisfaction, and job satisfaction has a positive and significant effect on employee performance